2020
DOI: 10.1161/hypertensionaha.120.14973
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Heritability, and Relation With Gene Expression of Novel DNA Methylation Loci for Blood Pressure

Abstract: We conducted an epigenome-wide association study meta-analysis on blood pressure (BP) in 4820 individuals of European and African ancestry aged 14 to 69. Genome-wide DNA methylation data from peripheral leukocytes were obtained using the Infinium Human Methylation 450k BeadChip. The epigenome-wide association study meta-analysis identified 39 BP-related CpG sites with P <1×10 −5 . In silico replication in the CHARGE consortium of 17 010 individuals validated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…Although our study failed to show significant associations of clinic BPs with specific MRs after correction for FDR <0.05, previous studies have reported associations of DNA methylation at several genomic loci in whole blood with clinic BP levels in thousands of subjects. 7,11,34 Several of these CpG sites were associated with various BP phenotypes in our study with marginal significance, demonstrating consistency with prior studies. However, despite the strengths of our methods of MR analysis, the sample size may have limited the statistical power for identifying significant associations between DNA methylation and clinic BP in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Although our study failed to show significant associations of clinic BPs with specific MRs after correction for FDR <0.05, previous studies have reported associations of DNA methylation at several genomic loci in whole blood with clinic BP levels in thousands of subjects. 7,11,34 Several of these CpG sites were associated with various BP phenotypes in our study with marginal significance, demonstrating consistency with prior studies. However, despite the strengths of our methods of MR analysis, the sample size may have limited the statistical power for identifying significant associations between DNA methylation and clinic BP in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Pre-eclampsia is strongly associated with later-life blood pressure, and (oddly) inversely associated with smoking [ 37 ]. We examined previous analyses of DNA methylation for high blood pressure [ 38 ] and smoking [ 39 ] in this cohort, and did not identify any overlapping differentially methylated sites (Additional file 1 : Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…All three twin cohorts have been studied in an intensive longitudinal manner, and several subprojects have been conducted in laboratory conditions. All twins who had taken part in clinical in-person sub-studies with sampling for both whole blood and muscle tissue, subsequent DNA methylation analyses and phenotype collection were included ( N = 139) [ 39 , 40 ]. The dataset comprises two age groups: young adults from 23 to 44 years of age ( N = 93) and older adults from 57 to 69 years of age ( N = 46).…”
Section: Methodsmentioning
confidence: 99%